Carbon-ceramic brake disc with coating abrasion indication mark and preparation method of carbon-ceramic brake disc
By setting different colors of wear indicator marks on the carbon ceramic brake disc, and using the color change of the mark to determine the wear amount of the coating, the complexity and unreliability of determining the wear amount of the carbon ceramic brake disc in the prior art are solved. A simple and accurate judgment of wear amount is achieved.
Patent Information
- Application Number
- CN202411612173.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-12
- Publication Date
- 2025-02-18
AI Technical Summary
The prior art is difficult to accurately and simply determine the wear amount of carbon ceramic brake disc coating. Conventional methods rely on external equipment and are complex in structure and are unreliable.
The wear indicator is set on the surface of the carbon-carbon matrix, consisting of two beveled thin cylinders or elliptical cylinders of different colors. The height of the first and second sheets is equal to the thickness of the carbon ceramic coating, and through wear The color change of the indicator mark determines the wear amount of the coating.
It realizes that the wear amount of carbon ceramic brake disc coating can be intuitively judged without external equipment. The method is simple, the cost is low, and the identification results are reliable, ensuring driving safety.
Smart Images

Figure CN119467566A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of carbon-ceramic brake discs, and in particular relates to a carbon-ceramic brake disc with a coating wear indicator mark and a preparation method thereof. Background Art
[0002] After long-term use, the carbon-ceramic coating on the surface of carbon-ceramic brake discs will gradually wear out. If the carbon-ceramic layer is worn too thin, it will affect driving safety. Therefore, it is necessary to determine the wear condition of the coating before the brake disc reaches its life span, so as to replace the brake disc with a new one when it is near its life limit to ensure driving safety. Conventional technology uses external electronic or mechanical measuring equipment to measure the thickness of the brake disc and other data to judge the amount of wear on the coating.
[0003] However, conventionally, when the amount of brake disc wear is determined by external measuring equipment, the detection method has many steps to implement and a complex structure, which leads to a high probability of system unreliability and problems, making it impossible to accurately and simply determine the amount of wear on the carbon-ceramic brake disc coating. Summary of the invention
[0004] The purpose of the present invention is to provide a carbon-ceramic brake disc with a coating wear indicator mark and a preparation method thereof. The carbon-ceramic brake disc with a coating wear indicator mark provided by the present invention can intuitively judge the wear amount of the carbon-ceramic brake disc coating without the aid of external equipment. The implementation method is easy, the additional cost is low, and the identification result is reliable.
[0005] In order to achieve the above object, the present invention provides the following technical solutions:
[0006] The present invention provides a carbon-ceramic brake disc with a coated wear indicator mark, comprising a carbon-carbon substrate 2 and a carbon-ceramic coating 1 and a wear indicator mark 3 arranged on the surface of the carbon-carbon substrate 2; the carbon-ceramic coating 1 covers the surface of the carbon-carbon substrate 2 except the wear indicator mark 3; the wear indicator mark 3 is composed of a first layer 31 and a second layer 32, the first layer 31 and the second layer 32 are beveled thin cylinders or beveled thin elliptical cylinders of the same shape, the cross-sections of the first layer 31 and the second layer 32 are in contact, the heights of the first layer 31 and the second layer 32 are both equal to the thickness of the carbon-ceramic coating 1, the bottom surface of the second layer 32 is in contact with the surface of the carbon-carbon substrate 2, and the colors of the first layer 31 and the second layer 32 are different.
[0007] Preferably, when the first sheet layer 31 and the second sheet layer 32 are obliquely cut thin cylinders of the same shape, the bottom diameters of the first sheet layer (31) and the second sheet layer (32) are 10 to 20 mm.
[0008] Preferably, the thickness of the wear indicator mark 3 and the carbon ceramic coating 1 is 0.5-1 mm.
[0009] The present invention provides a method for preparing a carbon-ceramic brake disc with a coating wear indicator as described in the above technical solution, comprising the following steps:
[0010] Bonding the rough wear indicator mark to the surface of the carbon-carbon matrix 2 to obtain the carbon-carbon matrix 2 with the rough wear indicator mark on the surface;
[0011] The remaining surface of the carbon-carbon matrix 2 with the wear indication mark on the surface is coated with coating powder, and then heated and hot-pressed to obtain a semi-finished product;
[0012] The semi-finished product is ceramicized to obtain the carbon-ceramic brake disc with the coating wear indicator mark.
[0013] Preferably, the method for preparing the initial embryo of the wear indicator mark comprises the following steps:
[0014] The cut surfaces of the first sheet embryo and the second sheet embryo are glued together and then hot-pressed. After cooling, they are cut and polished to obtain the wear indicator mark embryo. The hot-pressing pressure is 15 to 20 MPa, the temperature is ≥150° C., and the pressing time is 15 to 30 min.
[0015] Preferably, the material of the first sheet embryo includes carbon-carbon composite material or silicon carbide; the material of the second sheet embryo includes carbon fiber cloth, silicon carbide or carbon-carbon composite material.
[0016] Preferably, the material of the carbon-carbon matrix 2 is a carbon-carbon composite material; the coating powder includes silicon carbide powder and a binder; the mass ratio of the silicon carbide powder to the binder is (8-10):1.
[0017] Preferably, the mass ratio of the carbon-carbon matrix 2 to the silicon carbide powder is (55-65):(8-10).
[0018] Preferably, the ceramic treatment comprises the following steps: heating the semi-finished product and silicon powder for ceramic treatment, the holding temperature of the ceramic treatment is 1400-1700° C., and the holding time is 1-4 hours.
[0019] Preferably, the mass ratio of the carbon-carbon matrix 2 and the silicon powder in the semi-finished product is (55-65):(20-30).
[0020] The present invention provides a carbon-ceramic brake disc with a coated wear indicator mark, comprising a carbon-carbon substrate 2 and a carbon-ceramic coating 1 and a wear indicator mark 3 arranged on the surface of the carbon-carbon substrate 2; the carbon-ceramic coating 1 covers the surface of the carbon-carbon substrate 2 except the wear indicator mark 3; the wear indicator mark 3 is composed of a first layer 31 and a second layer 32, the first layer 31 and the second layer 32 are beveled thin cylinders or beveled thin elliptical cylinders of the same shape, the cross-sections of the first layer 31 and the second layer 32 are in contact, the heights of the first layer 31 and the second layer 32 are both equal to the thickness of the carbon-ceramic coating 1, the bottom surface of the second layer 32 is in contact with the surface of the carbon-carbon substrate 2, and the colors of the first layer 31 and the second layer 32 are different. The present invention aims at the shortcomings of the common external detection schemes, such as the multiple implementation steps and complex structure, and the inability to determine the amount of wear in the existing schemes. By directly setting a wear indicator mark 3 on the surface of the carbon-carbon substrate 2 (disc body), the wear indicator mark 3 is used to obtain an indicator mark that can visually determine the amount of wear of the coating, which is different from the carbon-ceramic coating 1, according to the change in the area of the first layer 31 or the second layer 32 during the wear process. Specifically, the quantitative wear thickness of the carbon-ceramic coating 1 is obtained according to the relationship between the change in the area of the first layer 31 or the second layer 32 and the layer height. Therefore, the present invention solves the problem that it is difficult to determine the amount of wear of the carbon-ceramic brake disc coating during installation and use, and the user can easily and simply determine the remaining service life of the coating. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 A schematic diagram of the partial structure of a carbon-ceramic brake disc with a coating wear indicator provided by the present invention;
[0022] Figure 2 A schematic diagram of the structure of a carbon-ceramic brake disc with a coating wear indicator provided in Example 1 of the present invention;
[0023] Figure 3 A schematic diagram of the structure of a carbon-ceramic brake disc with a coating wear indicator provided in Example 2 of the present invention;
[0024] Figure 4 A schematic structural diagram of a carbon-ceramic brake disc with a coating wear indicator provided in Example 3 of the present invention;
[0025] Figure 5 A physical picture of the wear condition of the carbon-ceramic brake disc with a coating wear indicator provided in Example 1 of the present invention;
[0026] Figure 6 A physical picture of the wear condition of a carbon-ceramic brake disc with a coating wear indicator provided in Example 2 of the present invention;
[0027] Figure 7A physical picture of the wear condition of a carbon-ceramic brake disc with a coating wear indicator provided in Example 3 of the present invention;
[0028] In the figure: 1 is a carbon ceramic coating, 2 is a carbon-carbon matrix, 3 is a wear indicator mark; 31 is a first layer, and 32 is a second layer. DETAILED DESCRIPTION
[0029] The present invention provides a carbon-ceramic brake disc with a coated wear indicator mark, comprising a carbon-carbon substrate 2 and a carbon-ceramic coating 1 and a wear indicator mark 3 arranged on the surface of the carbon-carbon substrate 2; the heights of the first layer 31 and the second layer 32 are equal to the thickness of the carbon-ceramic coating 1, and the carbon-ceramic coating 1 covers the surface of the carbon-carbon substrate 2 except the wear indicator mark 3; the wear indicator mark 3 is composed of the first layer 31 and the second layer 32, the first layer 31 and the second layer 32 are beveled thin cylinders or beveled thin elliptical cylinders of the same shape, the cross-sections of the first layer 31 and the second layer 32 are in contact, the bottom surface of the second layer 32 is in contact with the surface of the carbon-carbon substrate 2, and the colors of the first layer 31 and the second layer 32 are different.
[0030] In the present invention, unless otherwise specified, all preparation raw materials / components are commercially available products well known to those skilled in the art.
[0031] Figure 1 This is a schematic diagram of the structure of a carbon-ceramic brake disc with a coating wear indicator provided by the present invention. Figure 2 , Figure 3 and Figure 4 The structure diagram of the carbon ceramic brake disc with a coating wear indicator mark capable of displaying the specific structure of the wear indicator mark 3 provided in the embodiment of the present invention is shown below in combination with Figure 1 , Figure 2 , Figure 3 and Figure 4 The carbon-ceramic brake disc with coating wear indicator provided by the present invention is described in detail.
[0032] The carbon-ceramic brake disc with a coating wear indicator provided by the present invention comprises a carbon-carbon matrix 2. In the present invention, the carbon-carbon matrix 2 is in the shape of a ring of a carbon-ceramic brake disc. The material of the carbon-carbon matrix 2 is a carbon-carbon composite material.
[0033] In the present invention, the preparation method of the carbon-carbon composite material includes the following steps: stacking and laying a carbon fiber mesh and a carbon fiber non-woven cloth colloid layer and then needle-punching to obtain a needle-punched preform; carbon densifying the needle-punched preform to obtain a carbon-carbon preform; heat-treating the carbon-carbon preform to obtain the carbon-carbon composite material. The present invention has no special requirements for the specific implementation scheme of the carbon-carbon composite material, and it can be carried out in a manner familiar to those skilled in the art.
[0034] The carbon-ceramic brake disc with a coated wear indicator provided by the present invention comprises a carbon-ceramic coating 1 arranged on the surface of the carbon-carbon substrate 2. In the present invention, the material of the carbon-ceramic coating 1 is silicon carbide. The thickness of the carbon-ceramic coating 1 is preferably 0.5 to 1 mm. The carbon-ceramic coating 1 is arranged on the two annular surfaces of the carbon-carbon substrate 2. The carbon-ceramic coating 1 covers the surface of the carbon-carbon substrate 2 except the wear indicator 3.
[0035] The carbon-ceramic brake disc with coated wear indicator marks provided by the present invention comprises a wear indicator mark 3 arranged on the surface of the carbon-carbon matrix 2.
[0036] In the present invention, the wear indicator mark 3 is composed of a first layer 31 and a second layer 32, the first layer 31 and the second layer 32 are beveled thin cylinders or beveled thin elliptical cylinders of the same shape, the cross-sections of the first layer 31 and the second layer 32 are in contact, the bottom surface of the second layer 32 is in contact with the surface of the carbon-carbon matrix 2, and the colors of the first layer 31 and the second layer 32 are different.
[0037] In the present invention, the first sheet layer 31 and the second sheet layer 32 have the same shape. The heights of the first sheet layer 31 and the second sheet layer 32 are both equal to the thickness of the carbon ceramic coating 1. The height of the first sheet layer 31 or the second sheet layer 32 (denoted as h) is the vertical distance between the highest point of the section of the first sheet layer 31 or the second sheet layer 32 and the bottom surface.
[0038] In the present invention, the shape of the first layer 31 and the second layer 32 is a three-dimensional figure formed by cutting from the upper edge (edge of the upper surface) to the lower edge (edge of the lower surface) of a cylinder or an elliptical cylinder. The cut surface of the first layer 31 and the cut surface of the second layer 32 are in contact to obtain a complete cylinder or a complete elliptical cylinder. The height of the wear indicator mark 3 is equal to the height of the first layer 31 or the height of the second layer 32. The height of the wear indicator mark 3 is equal to the thickness of the carbon ceramic coating 1.
[0039] In a specific embodiment of the present invention, in the present invention, the first sheet 31 and the second sheet 32 are thin oblique cylinders of the same shape. The shape of the first sheet 31 and the second sheet 32 is a three-dimensional figure formed by cutting from the upper edge (edge of the upper surface) to the lower edge (edge of the lower surface) of the cylinder with the cylinder axis at α. The bottom diameter of the cylinder is d, and tanα=d / h.
[0040] In the present invention, the first layer 31 and the second layer 32 have different colors by making the material of the first layer 31 different from that of the second layer 32. When the carbon-ceramic brake disc with the coating wear indicator mark is not in use, the color of the damage indicator mark 3 is the color of the first layer 31. During the use of the carbon-ceramic brake disc with the coating wear indicator mark, as the carbon-ceramic coating 1 on the surface of the carbon-carbon matrix 2 is worn, the thickness of the damage indicator mark 3 becomes thinner, the first layer 31 is gradually worn, and the color of the second layer 32 begins to appear. As the degree of wear deepens, the exposed area of the first layer 31 decreases, and the exposed area of the second layer 32 increases. When the carbon-ceramic coating 1 on the surface of the carbon-ceramic brake disc with the coating wear indicator mark is basically worn out, the first layer 31 is also basically worn out, and the second layer 32 shows the largest area.
[0041] In the present invention, when the first layer (31) and the second layer (32) are beveled thin cylinders of the same shape, the bottom diameters of the first layer 31 and the second layer 32 are preferably 10 to 20 mm, more preferably 15 mm. The thickness of the wear indicator 3 is preferably 0.5 to 1 mm.
[0042] The present invention provides a method for preparing a carbon-ceramic brake disc with a coating wear indicator as described in the above technical solution, comprising the following steps:
[0043] Bonding the wear indicator mark embryo onto the surface of the carbon-carbon matrix 2 to obtain the carbon-carbon matrix 2 with the wear indicator mark embryo disposed on the surface;
[0044] The remaining surface of the carbon-carbon matrix 2 with the wear indication mark on the surface is coated with coating powder, and then heated and hot-pressed to obtain a semi-finished product;
[0045] The semi-finished product is ceramicized to obtain the carbon-ceramic brake disc with the coating wear indicator mark.
[0046] In the present invention, the wear indicator mark embryo is bonded to the surface of the carbon-carbon matrix 2 to obtain the carbon-carbon matrix 2 with the wear indicator mark embryo arranged on the surface.
[0047] In the present invention, the method for preparing the wear indicator blank preferably comprises the following steps:
[0048] The cut surfaces of the first sheet embryo and the second sheet embryo are glued together and then hot-pressed, and then cut and polished after cooling to obtain the wear indicator mark embryo; the hot-pressing pressure is 15-20MPa, the temperature is ≥150°C, and the pressing time is 15-30 minutes.
[0049] In the present invention, the material of the first sheet embryo preferably includes carbon-carbon composite material or silicon carbide. When the material of the first sheet embryo is preferably carbon-carbon composite material, the material of the first sheet obtained after the ceramic treatment is carbon-carbon composite material (wherein in the subsequent ceramic treatment process, due to the short ceramic treatment time, only the free carbon outside the carbon fiber will react, and the carbon fiber body will not react, so the material of the first sheet obtained after the ceramic treatment of the first sheet embryo is still carbon-carbon composite material). When the material of the first sheet embryo preferably includes silicon carbide, the material of the first sheet embryo is preferably a mixed material of silicon carbide and a binder, and the binder is preferably a liquid phenolic resin purchased from Shandong Yushi Ju Chemical, No. 6291A. The mass ratio of silicon carbide and binder is preferably (8-10): 1, more preferably 9: 1; the material of the first sheet obtained after the ceramic treatment is silicon carbide ceramic.
[0050] In the present invention, the material of the second sheet embryo preferably includes carbon fiber cloth, silicon carbide or carbon-carbon composite material. When the material of the second sheet embryo preferably includes carbon fiber cloth, the material of the second sheet embryo is preferably carbon fiber cloth and a first resin. The material of the second sheet obtained after the ceramic treatment is carbon fiber cloth. The first resin is preferably a liquid phenolic resin purchased from Shandong Yushiju Chemical Industry, No. 6291A.
[0051] In the present invention, when the material of the second sheet embryo preferably includes silicon carbide, the material of the second sheet embryo is preferably a mixed material of silicon carbide and a binder, and the binder is preferably a liquid phenolic resin purchased from Shandong Yushiju Chemical Industry, No. 6291A. The mass ratio of the silicon carbide to the binder is preferably (8-10):1, more preferably 9:1; the material of the second sheet obtained after the ceramic treatment is silicon carbide.
[0052] In the present invention, when the material of the second sheet embryo is preferably a carbon-carbon composite material, the material of the second sheet obtained after the ceramic treatment is a carbon-carbon composite material.
[0053] The preparation method of the carbon-carbon composite material has been described above and will not be repeated here.
[0054] The cut surfaces of the first sheet embryo and the second sheet embryo are preferably bonded by a second resin adhesive. The second resin is preferably a liquid phenolic resin purchased from Shandong Yushi Ju Chemical Industry, No. 6291A. In the present invention, the hot pressing preferably places the first sheet 31 and the second sheet 32 after bonding into a mold and presses them using a hot press. The pressure of the hot pressing is preferably 15 to 20 MPa, the temperature is preferably ≥150°C, more preferably 150°C, and the pressing time is preferably 15 to 30 min. The present invention has no special requirements for the specific implementation of the cutting and grinding.
[0055] In the present invention, the shape of the carbon-carbon matrix 2 is annular. The annular carbon-carbon matrix 2 is preferably obtained by machining a carbon-carbon composite material plate. The preparation method of the carbon-carbon composite material plate is the same as the preparation method of the carbon-carbon composite material mentioned above, which will not be repeated here. The wear indicator mark 3 is preferably bonded to the surface of the carbon-carbon matrix 2 by a third resin. The third resin is preferably a liquid phenolic resin purchased from Shandong Yushi Ju Chemical, No. 6291A. In the present invention, the mass ratio of the total mass of the first resin, the second resin and the third resin to the carbon-carbon matrix 2 is preferably (2~4): (55~65).
[0056] After obtaining the carbon-carbon substrate 2 with the wear indicator mark 3 on the surface, the present invention coats the remaining surface of the carbon-carbon substrate 2 with the wear indicator mark 3 on the surface with coating powder, heats it, and performs hot pressing and curing to obtain a semi-finished product.
[0057] In the present invention, the coating powder preferably includes silicon carbide powder and a binder. The binder is preferably a liquid phenolic resin purchased from Shandong Yushi Ju Chemical, No. 6291A. The mass ratio of the silicon carbide powder and the binder is preferably (8-10):1, more preferably 9:1. The mass ratio of the carbon-carbon matrix 2 to the silicon carbide powder is preferably (55-65):(8-10), more preferably 60:9. In the present invention, the coating thickness of the coating powder is preferably 1.5-2 mm. When the thickness of the wear indicator mark 3 is less than the thickness of the carbon ceramic coating 1, the present invention preferably further includes coating the coating powder on the surface of the wear indicator mark 3, and the thickness of the coating powder coated on the surface of the wear indicator mark 3 is the difference between the thickness of the coating powder coated on the surface of the carbon-carbon matrix 2 and the thickness of the wear indicator mark 3. As one or more embodiments of the present invention, the coating thickness of the coating powder is greater than the indicator mark by 0.5-2 mm, covering the indicator mark.
[0058] The present invention has no special requirements on the specific implementation process of the coating. After the hot pressing curing treatment, the indicator mark is exposed by grinding.
[0059] In the present invention, the pressure of the hot pressing curing is preferably 15 to 25 MPa, the temperature is preferably 150 to 200° C., and the curing time is preferably 30 to 60 min.
[0060] After obtaining the semi-finished product, the present invention performs a ceramic treatment on the semi-finished product to obtain the carbon-ceramic brake disc with the coating wear indicator mark.
[0061] In the present invention, the ceramic treatment preferably includes the following steps: placing the semi-finished product and silicon powder in a crucible, and then heating for ceramic treatment. The mass ratio of the carbon-carbon matrix 2 and the silicon powder in the semi-finished product is preferably (55-65): (20-30), and more preferably 60:30. The holding temperature of the ceramic treatment is preferably 1400-1700°C, and the holding time is preferably 1-4h, and more preferably 2h.
[0062] In the present invention, the crude brake disc obtained by the ceramic treatment is preferably further polished to make the surface smooth and expose the complete wear indicator mark 3 to obtain the carbon ceramic brake disc with a coating wear indicator mark. After obtaining the carbon ceramic brake disc with a coating wear indicator mark, the present invention packs and stores the qualified products after machining the carbon ceramic brake disc with a coating wear indicator mark.
[0063] The preparation method of the carbon-ceramic brake disc with a coating wear indicator provided by the present invention includes: processing the brake disc substrate, making and bonding the indicator, coating processing, ceramicization, fine machining of the appearance, and obtaining the finished product. Aiming at the shortcomings of the common external detection schemes, which have many implementation steps and complex structural composition, and the existing schemes cannot determine the amount of wear, the present invention adopts a method of directly bonding the coating wear indicator on the disc body and ceramicizing it together with the disc body to make an indicator that can visually determine the amount of coating wear, which is different from the carbon-ceramic coating, thereby solving the problem that the amount of coating wear of the carbon-ceramic brake disc during installation and use is difficult to determine, and the user can easily and clearly determine the remaining service life of the coating.
[0064] In order to further illustrate the present invention, the technical solutions provided by the present invention are described in detail below in conjunction with embodiments, but they should not be construed as limiting the protection scope of the present invention.
[0065] The following examples are based on Figure 1 The structure of the carbon-ceramic brake disc with coating wear indicator mark is prepared.
[0066] Example 1
[0067] The method for preparing a carbon-ceramic brake disc with a coating wear indicator provided in this embodiment specifically comprises the following steps:
[0068] (1) Brake disc matrix processing: The carbon-carbon composite material sheet is machined and turned into a 60 weight part brake disc matrix, namely Figure 1 The carbon-carbon matrix 2.
[0069] (2) Production and bonding of wear indicator marks: Purchase soft carbon felt with a density of 0.14-0.18 g / cm 3 , soak it in 6291A phenolic resin liquid (the mass ratio of alcohol to resin is 1:1 to 1:1.2), then take it out and dry it to obtain a carbon fiber cloth mixed with resin material.
[0070] The carbon fiber cloth mixed resin material with an inclined cross section of equal thickness (the second layer embryo) and the beveled cross section of the carbon-carbon composite material plate (the first layer embryo) are bonded together with resin (liquid phenolic resin, purchased from Shandong Yushiju Chemical, type No. 6291A), put into a mold, heated to 150°C using a press, and pressed for 30 minutes at a pressure of 20MPa. After pressing, it is taken out of the mold, and after cooling, it is cut and polished into small discs with a diameter of 15mm (thickness of 0.5-1mm), which is Figure 1 The wear indicator mark 3 is polished and smoothed, and then glued to the friction surface of the brake disc substrate (carbon-carbon substrate 2) obtained in step (1) with resin (liquid phenolic resin, purchased from Shandong Yushiju Chemical Industry, No. 6291A).
[0071] (3) Coating processing: 10 parts by weight of silicon carbide powder and 1 part by weight of a binder (liquid phenolic resin purchased from Shandong Yushiju Chemical Industry Co., Ltd., No. 6291A) were mixed evenly to obtain a powder. The disc body of step (2) was placed in a mold and covered with the powder. The coating thickness was 1.5 to 2 mm, covering the wear indicator mark 3. A press was used to pressurize and heat both sides of the disc body at a pressure of 25 MPa and a temperature of 200°C for 60 min, and then the surface was polished to make it smooth.
[0072] (4) Ceramics: Place the brake disc obtained in step (3) in a crucible, sprinkle 30 parts by weight of silicon powder on the center of the bottom of the crucible, place it in a furnace and gradually heat it to 1700°C, keep it warm for 2 hours, then slowly cool it down and take it out after it is completely cooled.
[0073] (5) Shape machining: After the ceramicization in step (4), the surface of the brake disc is polished and smoothed to expose the complete wear indicator mark, thereby obtaining a carbon ceramic brake disc with a coated wear indicator mark.
[0074] (6) Finished product: The carbon ceramic brake disc with coating wear indicator obtained in step (5) is machined and inspected to be qualified products, which are packaged and stored as finished products.
[0075] In this embodiment, the mass fraction of each raw material used in step (1) to step (4) is: 60 parts of carbon-carbon composite material in step (1), 10 parts of silicon carbide used in step (3), 30 parts of silicon powder used in step (4), the total mass of the resin used in step (2) accounts for 4% of the total mass of the indicator mark, 1 part of the binder used in step (3), and 0.1 part of carbon fiber cloth (soft carbon felt) used in step (2).
[0076] The wear indicator in step (2) of this embodiment is made of a carbon-carbon composite material plate (first layer) with a volume percentage of 50% and a carbon fiber cloth (second layer) with a volume percentage of 50% and resin bonded, and cut and polished into the following shapes: Figure 2 The chamfered surface where two materials meet in the middle is a disc with a diameter of 15 mm and a thickness of 0.8 to 1.0 mm. Figure 2 In the embodiment, the material of the first layer 31 is a carbon-carbon composite material, and the material of the second layer 32 is a carbon fiber cloth. The wear indicator mark 3 of the friction surface of the carbon ceramic brake disc with a coated wear indicator mark prepared in this embodiment is shown in the figure. Figure 5 As shown in the left figure, as the use time increases, when the carbon ceramic coating 1 of the carbon ceramic brake disc is worn, the wear indicator 3 of the carbon ceramic brake disc will be as follows: Figure 5 As shown in the middle and right pictures in the figure. Figure 5 The middle image in the figure and the area of the second layer in the right image, or by visual inspection Figure 5 From the middle picture in the figure and the remaining area of the first layer in the right picture, we can conclude that: Figure 5 The middle figure in the figure shows that the carbon ceramic coating 1 of the carbon ceramic brake disc prepared in Example 1 is worn by 30% (percentage of thickness). Figure 5 The right figure in FIG. 1 shows that the carbon ceramic coating 1 of the carbon ceramic brake disc prepared in Example 1 is worn by 60%.
[0077] In this embodiment, the material of the first layer 31 is a carbon-carbon composite material, and the brake disc substrate is a carbon-carbon composite material plate. During the ceramicization process, only the free carbon outside the carbon fiber of the first layer 31 and the brake disc substrate reacts to generate silicon carbide, and the fiber body does not react. The reason for the different colors of the two is that the carbon content in the two materials is different.
[0078] Example 2
[0079] The preparation method of this embodiment is basically the same as that of the embodiment 1, except that the wear indicator mark 3 in this embodiment is made of 50% carbon-carbon composite material plate (first layer blank) and 50% silicon carbide plus binder mixture (second layer blank), cut and polished into Figure 3 The chamfered surface shown in the figure has a diameter of 15mm and a thickness of 0.5 to 1mm where two materials meet. Figure 3In the embodiment, the material of the first layer 31 is a carbon-carbon composite material, and the material of the second layer is silicon carbide. The wear indicator mark 3 on the friction surface of the carbon ceramic brake disc with a coating wear indicator mark prepared in this embodiment is shown in the figure below. Figure 6 As shown in the left figure, as the use time increases, when the carbon ceramic coating 1 of the carbon ceramic brake disc is worn, the wear indicator 3 of the carbon ceramic brake disc will be as follows: Figure 6 As shown in the middle and right pictures in the figure. Figure 6 From the middle picture in the figure and the remaining area of the first layer in the right picture, we can conclude that: Figure 6 The middle figure in the figure shows that the carbon ceramic coating 1 of the carbon ceramic brake disc prepared in Example 2 is worn by 30%. Figure 6 The right figure in FIG. 2 shows that the carbon ceramic coating 1 of the carbon ceramic brake disc prepared in Example 2 is worn by 60%.
[0080] Example 3
[0081] The preparation method of this embodiment is basically the same as that of the embodiment 1, except that the wear indicator mark 3 in this embodiment is made of 50% silicon carbide plus a binder mixture (first layer embryo) and 50% carbon-carbon composite material plate (second layer embryo), which is cut and polished into Figure 4 The chamfered surface shown in the figure has a diameter of 15mm and a thickness of 0.5 to 1mm where two materials meet. Figure 4 In the embodiment, the material of the first layer 31 is silicon carbide, and the material of the second layer is a carbon-carbon composite material. The wear indicator mark 3 of the friction surface of the carbon ceramic brake disc with a coating wear indicator mark prepared in this embodiment is shown in the figure below. Figure 7 As shown in the left figure, as the use time increases, when the carbon ceramic coating 1 of the carbon ceramic brake disc is worn, the wear indicator 3 of the carbon ceramic brake disc will be as follows: Figure 7 As shown in the middle and right pictures in the figure. Figure 7 From the middle picture in the figure and the area of the second layer exposed in the right picture, we can conclude that: Figure 7 The middle figure in the figure shows that the carbon ceramic coating 1 of the carbon ceramic brake disc prepared in Example 3 is worn by 30%. Figure 7 The right figure in FIG. 3 shows that the carbon ceramic coating 1 of the carbon ceramic brake disc prepared in Example 3 is worn by 60%.
[0082] The raw materials for preparing the wear indicator mark 3 in Examples 1 to 3 are shown in Table 1.
[0083] Table 1 Raw materials for preparing the wear indicator mark 3 in Examples 1 to 3
[0084]
[0085] At present, conventional carbon-ceramic brake discs rely on external measuring equipment to determine the amount of wear on the brake disc. The structure and principle are relatively complex, resulting in a high probability of system unreliability and problems. The present invention directly adds indicator marks on the coating surface, so that users can directly and quickly determine the approximate amount of wear on the coating. From the above embodiments, it can be seen that the method provided by the present invention adopts a method of directly combining and producing a simple and easy-to-identify carbon-ceramic coating wear indication area on the disc body, which can intuitively determine the amount of wear on the carbon-ceramic brake disc coating without the aid of external equipment. The implementation method is easy, the additional cost is low, and the identification result is reliable.
[0086] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. Other embodiments can be obtained based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.
Claims
1. A carbon ceramic brake disc with a coating wear indicator, characterized in that: The invention comprises a carbon-carbon substrate (2), a carbon ceramic coating (1) and a wear indicator (3) arranged on the surface of the carbon-carbon substrate (2); the carbon ceramic coating (1) covers the surface of the carbon-carbon substrate (2) except the wear indicator (3); the wear indicator (3) is composed of a first layer (31) and a second layer (32); the first layer (31) and the second layer (32) are beveled thin cylinders or beveled thin elliptical cylinders of the same shape; the cross sections of the first layer (31) and the second layer (32) are in contact; the heights of the first layer (31) and the second layer (32) are both equal to the thickness of the carbon ceramic coating (1); the bottom surface of the second layer (32) is in contact with the surface of the carbon-carbon substrate (2); and the colors of the first layer (31) and the second layer (32) are different.
2. The carbon-ceramic brake disc with a coating wear indicator according to claim 1, characterized in that: When the first sheet layer (31) and the second sheet layer (32) are obliquely cut thin cylinders of the same shape, the bottom diameters of the first sheet layer (31) and the second sheet layer (32) are 10 to 20 mm.
3. The carbon-ceramic brake disc with a coating wear indicator according to claim 1 or 2, characterized in that: The thickness of the carbon ceramic coating (1) is 0.5 to 1 mm.
4. The method for preparing a carbon-ceramic brake disc with a coating wear indicator according to any one of claims 1 to 3, characterized in that: The following steps are involved: Bonding the rough wear indicator mark to the surface of a carbon-carbon matrix (2) to obtain a carbon-carbon matrix (2) having the rough wear indicator mark provided on the surface; The remaining surface of the carbon-carbon matrix (2) provided with the wear indication mark is coated with coating powder, and then heated and hot-pressed to solidify to obtain a semi-finished product; The semi-finished product is ceramicized to obtain the carbon-ceramic brake disc with the coating wear indicator mark.
5. The preparation method according to claim 4, characterized in that: The method for preparing the initial embryo of the wear indicator mark comprises the following steps: The cut surfaces of the first sheet embryo and the second sheet embryo are glued together and then hot-pressed, and then cut and polished after cooling to obtain the wear indicator mark embryo; the hot-pressing pressure is 15-20 MPa, the temperature is ≥150° C., and the pressing time is 15-30 min.
6. The carbon-ceramic brake disc with coating wear indicator according to claim 5, characterized in that: The material of the first sheet embryo includes carbon-carbon composite material or silicon carbide; the material of the second sheet embryo includes carbon fiber cloth, silicon carbide or carbon-carbon composite material.
7. The preparation method according to claim 4, characterized in that: The material of the carbon-carbon matrix (2) is a carbon-carbon composite material; the coating powder comprises silicon carbide powder and a binder; the mass ratio of the silicon carbide powder to the binder is (8-10):
1.
8. The preparation method according to claim 7, characterized in that: The mass ratio of the carbon-carbon matrix (2) to the silicon carbide powder is (55-65):(8-10).
9. The preparation method according to claim 4, characterized in that: The ceramic treatment comprises the following steps: heating the semi-finished product and silicon powder for ceramic treatment, wherein the thermal insulation temperature of the ceramic treatment is 1400-1700° C. and the thermal insulation time is 1-4 hours.
10. The preparation method according to claim 9, characterized in that: The mass ratio of the carbon-carbon matrix (2) and the silicon powder in the semi-finished product is (55-65):(20-30).